Pengaruh Tax Avoidance Terhadap Cost Of Debt Dan Dampaknya Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2015-2017) - Raden Wulan Saparinda (Jurnal Accounting Information System (AIMS), 2020)
The purpose of this research  is to analyze tax avoidance on the cost of debt and it affects the firm value. This research uses a sample of manufacturing companies on the Indonesia Stock Exchange for the period 20152017. The program used in analyzing data uses  SPSS  21 . This research found that tax avoidance has a positive influence on the cost of debt t test showing significance of 0.003 <0.05. Cost of Debt has a negative effect on firm value with a significance of 0,000 <0,05. Tax avoidance does not affect on firm value because of the significance of 0.052> 0.05. The cost of debt can mediate the effect of tax avoidance on firm value with a significance of 0.025 <0.05. The path analysis results is a direct effect of X on Y by 9,1%, direct effect of Y on Z by 15,84% and there is an indirect effect of X on Z through Y by  -12%.